Quantum phenomena in the radial thermal expansion of bundles of single-walled carbon nanotubes doped with 3He. A giant isotope effect - Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Vinnikov, N.A.; Popov, S.N.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The radial thermal expansion αr of bundles of single-walled carbon nanotubes saturated with 3He up to the molar concentration 9.4% has been investigated in the temperature interval 2.1–9.5 K by high-sensitivity capacitance dilatometry. In the interval 2.1–7 K a negative αr was observed, with a magnitude which exceeded thelargest negative αr values of pure and 4He-saturated nanotubes by three and two orders of magnitude, respectively. The contributions of the two He isotope impurities to the negative thermal expansion of the nanotube bundlesare most likely connected with the spatial redistribution of 4He and 3He atoms by tunneling at the surface and insidenanotube bundles. The isotope effect turned out to be huge, probably owing to the higher tunneling probability of 3He atoms.